Exploring celebrity endorsements : a comparative analysis of football and sport climbing for brand image enhancement - Rozsnyói, Soma (2024)
The main goal of this study is to examine the effect of celebrity endorsement on brand image while comparing this between one of the most popular sports, football, and a relatively niche sport, sports climbing. The research also explores whether and how the status of a celebrity endorser (active or retired) and the popularity of the sports athlete can influence the perception of the consumers of brand image. A quantitative approach was used in the form of an online survey to gather relevant data targeting specific audiences of both sports, which was later analyzed. The findings showed that active sports athletes have a more favorable impact on the brand image than retired athletes in both football and sports climbing. Furthermore, the study revealed that while sports popularity can influence the brand image, familiarity with the athlete has an important role as well. These insights indicate that marketers should advertise their brands with still-active athletes. Moreover, marketers should consider the target audience's familiarity with the athlete to enhance brand image. This study adds to the limited literature on niche sports endorsement strategies via the example of sports climbing and offers relevant knowledge for brands in choosing effective endorsers.